Quinone C–H Alkylations via Oxidative Radical Processes - Hamsath, Akil; Galloway, Jordan D.; Baxter, Ryan D. (Synthesis, 2018)
A brief survey of radical additions to quinones is reported. Carboxylic acids, aldehydes, and unprotected amino acids are compared as alkyl radical precursors for the mono- or bis- C–H alkylation of several quinones. Two methods for radical initiation are discussed comparing inorganic persulfates and Selectfluor as stoichiometric oxidants. Kinetic analysis reveals dramatic differences in the rate of radical initiation depending on the identity of the radical precursor and oxidant. Synthetic strategies for efficiently producing alkyl-quinones are discussed in the context of selecting optimum radical precursors and initiators depending on quinone identity and functional groups present.
Keywords: quinones; radicals; alkylation; Selectfluor; kinetics